Analysis Of Work Ethics, Job Loyalty, and Job Satisfaction On Employee Performance at The Binjai City Regional Inspectorate Office - Monica Fransiska Gultom; Kholilul Kholik (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the influence of work ethics, job loyalty, and job satisfaction on employee performance at the Regional Inspectorate Office of Binjai City. The research method used is quantitative with a causal associative approach. The research sample consisted of 65 employees, covering the entire population of State Civil Apparatus (ASN) at the institution. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results show that partially, work ethics have a positive and significant effect on performance (t = 6.785; p = 0.000), job loyalty has a positive and significant effect (t = 2.828; p = 0.006), and job satisfaction has a positive and significant effect (t = 3.527; p = 0.001). Simultaneously, the three independent variables also have a positive and significant effect on employee performance (F = 45.042; p = 0.000), contributing 67.4% (Adj. R² = 0.674). These findings indicate that improving the performance of government internal supervisory apparatus requires an integrated approach encompassing strengthening ethics, fostering loyalty, and creating job satisfaction.